2014
DOI: 10.2139/ssrn.2461292
|View full text |Cite
|
Sign up to set email alerts
|

Devolution and Governance Conflicts in Africa: Kenyan Scenario

Abstract: The interests on devolved system of government have increased over time in Africa. This paper looks at devolution and governance conflicts in Africa. The paper makes an attempt in assessing the likely conflicts from this system and possibly so their mitigations with the Kenyan scenario. The study applies the underlined objectives in achieving its goals. Ultimately, the paper will attempt to answer questions such as; what is devolution? Why devolution? What is the rationale of devolution? What are the likely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The most comprehensive was developed by the Public Service Commission of Kenya [PSCK] (2015) framework to operationalize the constitutional and other legal and regulatory provisions to enforce ethical standards in the public service. Despite the express constitutional provisions (Article 190) for cooperation between counties and national government, Juma et al (2014) observed that confusion still lingers whether devolution is decentralization or federalism which often led to antagonistic relationship and confusion about the actual point of responsibility and accountability. Devolution in Kenya had the immediate benefit of improved equity since public resources hitherto concentrated at the center were channeled to all 47 County governments leading to expanded services to the whole Country (Korir, Rotich & Bengat, 2015).…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
“…The most comprehensive was developed by the Public Service Commission of Kenya [PSCK] (2015) framework to operationalize the constitutional and other legal and regulatory provisions to enforce ethical standards in the public service. Despite the express constitutional provisions (Article 190) for cooperation between counties and national government, Juma et al (2014) observed that confusion still lingers whether devolution is decentralization or federalism which often led to antagonistic relationship and confusion about the actual point of responsibility and accountability. Devolution in Kenya had the immediate benefit of improved equity since public resources hitherto concentrated at the center were channeled to all 47 County governments leading to expanded services to the whole Country (Korir, Rotich & Bengat, 2015).…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
“…These revelations prompted the scholars to make a recommendation that the study of this magnitude should be conducted nationwide. As Juma et al (2014) advised, all stakeholders should guard devolution with a clear resolute such that past governance mistakes will be lessons for bettering Kenya through devolution. Muli (2014), while studying the difficulties of implementing the devolution approach in the Nairobi city county administration, uncovered the following: realized that the political and physical environment, resistance from Members of the County Assembly, employees, business community and the electorate were the main impediment towards the implementation of their devolution strategy.…”
Section: Stakeholder Involvement Practices and Devolved Administrativ...mentioning
confidence: 99%
“…Even with this carefully crafted guideline in our Constitution, there has been serious tensions regarding those functions and powers between the national and county governments (Kangu, 2015). Juma, Rotich, and Mulongo (2014) on their study about devolution and governance conflicts in Africa-Kenyan scenario, recommended that the governments should respect the basic principles of socio-eco-political justice, fully embrace constitutionalism for the realization of development, disregard the feeling of fiscal stress when implementing the stated percentage of devolved funds to counties and ensuring the existence of a uniform governance culture. Odero, Egessa, and Oseno (2019) discovered in their research on ithe imoderating effect of legal factorsionitheilinkibetweenistrategicileadershipipracticesiand performance of deposit takingiSACCO'siiniKenya, andithat the legalifactorsiindeedimoderated theilink between the strategicileadershipipracticesiand performance ofiDeposititakingiSACCOs.…”
Section: Legal Factors and Devolved Administrative Structuresmentioning
confidence: 99%
“…These revelations prompted the scholars to make a recommendation that, a similar study but with a wider scope be conducted nationwide inorder to have clear understanding of what governance requires. As Juma et al (2014) advised, all stakeholders should guard against a repeat of past governance mistakes if they are to improve Kenya through devolution.…”
Section: Literature Review Stakeholder Involvement Practices and Devo...mentioning
confidence: 99%